Removal of Toxic Hexavalent Chromium Ions from Aqueous Solution by a Natural Biomaterial: Batch and Column Adsorption - Fatma Gurbuz (Adsorption Science & Technology)
The results of the removal of chromium(VI) ions from the aqueous phase employing different algal biomasses as bio-adsorbents are presented. Batch and column experiments were performed to determine the maximum adsorption capacity of the selected adsorbents. Algae were immobilised by employing pumice or silica gel as alternative substances for polymer matrices. The effects of pH, contact time, initial Cr(VI) ion concentration and adsorbent concentration were tested. Results are presented showing that the maximum adsorption capacity occurred at pH 2 when Scenedesmus obliquus and Arthospira maxima were employed as adsorbents. A biphasic Cr(VI) ion removal pattern was observed in all experiments. The effects of Cr(VI) ion loading on both the free and immobilised biomass were tested to allow the applications to be compared. The maximum removal extent of Cr(VI) ions from the aqueous phase was 18.98 ± 0.32 mg/mg free S. obliquus and 18.37 ± 0.28 mg/mg immobilised S. obliquus. The results show that immobilisation of the biomaterial made only a small difference to the extent of Cr(VI) ion removal. However, it is a much more suitable process for industrial applications since it can be continuously applied. The recovery of loaded metal ions was studied when it was found that HCl was very effective for desorbing Cr(VI) ions adsorbed onto the biomass. The results indicate that S. obliquus biomass is a potential candidate for the development of an efficient adsorbent for the removal of Cr(VI) ions from wastewater.